Effect of Harvest Year and Altitude on Nutritional and Biometric Characteristics of Blueberry Cultivars - Sofia Correia; Berta Gonçalves; Alfredo Aires; Ademar Silva; Luís Ferreira; Rosa Carvalho; Hortense Fernandes; Cândida Freitas; Valdemar Carnide; Ana Paula Silva (Journal of Chemistry)
In recent years the consumption of small fruits has increased continuously and knowledge about the more suitable production requirements is essential. This study aims to evaluate the influence of harvest year and altitude on chemical composition of four blueberry cultivars, in order to create rentable opportunities for producers and minimize eventual losses in quality fruits. Dry mass, protein, fat, energy, free sugars, organic acids, and vitamin C contents were determined using HPLC-UV-DAD and spectrophotometric methods. Differences (p<0.05) in the concentrations of free sugars, organic acids, and vitamin C were found among years, while the altitude had no (p>0.05) influence. Citric acid was the main organic acid and fructose the most abundant sugar in blueberries. Fruits of “Ozarkblue” had the highest mass and volume whilst the “Bluecrop” was the cultivar with highest crude protein and fat contents. “Goldtraube” showed the highest content of sucrose and organic acids and “Duke” had the highest content of fructose.